Mixed Convection Heat Transfer Inside A vented Square Enclosure with Concentric Rotation Inner Cylinder (University of Thi-Qar Journal for Engineering Sciences, 2013)
Mixed convection heat transfer for laminar air flow inside a vented square enclosure with rotation inner cylinder is studied numerically The bottom wall is heated at constant temperature (Th ) while the other walls and the surfaces of the inner cylinder are adiabatic. An external flow enters the square cavity through an opening located down the left vertical wall and exits from an opening located in the upper right wall. The conservation governing equations (continuity, momentum and energy are solved by finite element method using Flex PDE software package. Results of velocity curves, isotherms and average Nusselt number show the effect of the variables: Richardson number (Ri = 0,6,10), Reynolds number (Re = 20, 50, 100 ), Prandtl number (Pr = 0.7), the dimensionless angular velocity (? = 0 –3) and dimensionless radius of rotating cylinder (R= 0 - 0.3) on heat transfer and flow filed. The results show that, the average Nusselt number increases with increasing Ri, Re, R and decreases with increasing ?. The results are compared with other authors in the literature and give a good agreement.